Relative Age effect in French alpine skiing: Problem and solution - De Larochelambert, Q.; Difernand, A.; Antero, J.; Sedeaud, A.; Toussaint, J.-F.; Yves, L. P.; Coulmy, N. (Journal of Sports Sciences, 2022)
This study aims to identify the potential bias of the relative age effect (RAE) in French alpine skiers and to propose a mathematical correction adjustment for such a bias. All performances and birthdates of skiers on the national and international circuit were collected from the 2004 up to 2019. A goodness-of-fit chi-square test and the residuals were used to study the distribution of birth trimesters in youth competitors. A linear relationship between the distribution of performances and the months obtains a calibration coefficient allowing to rebalance the performance by considering the effect of RAE. Individuals born at the beginning of the year are over-represented in the elite young selections in all disciplines for both genders. A coefficient based on the relationship between month of birth and performance adjusts individual performance and cancels out the effect of RAE. The results show that RAE is present in French alpine skiing. We present a method allowing to consider the effect of the RAE in the performances realized in each gender and discipline. This method allows coaches to have a more objective opinion on performance and to reduce selection bias.